(untitled) (Economics and region, 2021)
The system of economic security is considered a complex combination of short-term and long-term control systems. The necessity of interaction and simultaneous functioning of these two systems for ensuring adequate and operative assessment of the institution `s activity is characterized. The paper examines the need of using forecasting methods to ensure control and monitoring of financial institutions` economic security. The role of forecasting in the system of ensuring stable activity of the institution is determined. The advantages of introducing forecasting into the stability control system are presented. The main functions of forecasting and features of their realization in the conditions of uncertainty are allocated. The need for constant control and analysis of the main current indicators of the financial institution and forecasting their changes in the future. The forecast should be revised according to the new information at all analysis stages. The need for rapid adaptation of long-term plans and projects for the institution development in accordance with the results of forecasting. Forecasting is defined as an effective tool for ensuring the institution’s economic security.